Efektivitas Metode Diskusi terhadap Hasil Belajar Siswa dalam Pembelajaran IPS SD/MI - Afwa Shofatun Nisa; Iis Suharyati; Oman Farhurohman (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The aim of this research is to determine if the discussion method enhances student learning outcomes in social studies for SD/MI. A literature review approach was utilized to conduct this investigation. This method is based on several relevant articles that explore how discussion techniques influence learning outcomes in social studies at the SD and MI levels. Findings from various journals indicate that the discussion method significantly improves academic performance, and its implementation effectively boosts student achievement, particularly in social studies classes for elementary students.